Thiết bị đo nhiệt độ cao ORP - 16 và ORP - 16 - IC - Chau, Nguyen Van; Phuong, Nguyen Ky; Thang, Hoang Dac; Hung, Nguyen Thai (Journal of Computer Science and Cybernetics, 2018)
Thiết bị đo nhiệt độ cao ORP - 16 và ORP - 16 - IC